A comparative study of clinical methods and ultrasound methods for prediction of fetal birth weight at term gestation - Rashmi Khatri; Geetika Bhardwaj; Seema Rawal; Rajiv Ranjan Kumar; Neeru Malik (New Indian Journal of OBGYN)
Objectives: To compare the clinical and sonographic fetal weight estimation at term gestation. Methods: This prospective observational study included 500 antenatal women with singleton pregnancy with gestational age (GA) between 37-41 completed weeks delivering within 24 hours of admission and in labor or booked for elective caesarean section. Estimated fetal weight (EFW) was determined by three clinical methods (Leopold Manoeuvre, Johnson’s formula, and Dare’s formula) and ultrasound estimation (Hadlock’s formula). The calculated weight (by all methods) was considered accurate if they were within ±10% of actual birth weight (ABW). All the measurements were tabulated in a datasheet and compared with ABW after delivery of fetus. P-value <0.05 was considered statistically significant. Results: Absolute mean error in prediction of actual fetal weight was significantly different among different methods with highest mean error being with Johnson’s method (359.37±97.09) and lowest error being with Leopold’s method (212.65±69.99), with ultrasound (233±65.86) showing the value in between both of them with p-value <0.0001. For predicting actual birth weight within the range of 10% in total study subjects, ultrasound showed the best closest estimate with 90.8% cases followed by Leopold’s method with 87.80% cases, Johnson method (80.00%) and Dare’s method (79.00%) (p<0.0001). Conclusion: Clinical methods and USG are accurate in prediction of the ABW. Among clinical methods, Leopold’s maneuver was most accurate and comparable to USG. The accuracy of clinical method in comparison to sonographic method for prediction of actual birth weight may allow for its use in low resource settings.